PERANCANGAN BUKU POP-UP MENGENAI SOPAN SANTUN UNTUK ANAK - Haura Herlya, Drs. Ariusmedi, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The0purpose0of0this0design is to introduce children to polite comprehension. This comprehension is directly related to attitudes in children's daily lives.0One of the0media that can0help0this comprehension0is the pop-up book. This pop-up book can be an interactive, communicative and effective media in the effort to preserve manners in this globalization era. Users0of this0pop-up book can have a positive effect on children, because this book is designed so that it can attract the attention0of children in comprehension0manners easily. Not0only that the design of this book can help children to learn while playing. The Design Method in this0pop-up book is0Glass0Box0which is a design method related to design.0Data Analysis0Method used in the0design is to use 5W + 1H analysis, What, When, Where, Who, Why,0How to0make it easier to find solutions to problems0encountered. The0design0of this pop-up book is entitled0"Adit and Courtesy of0Politeness". This book is0designed using visual communication design theory, media, illustrations, colors, pop-up books, books, children's psychology, typography and layouts. In0addition to designing pop-up books0as the main media on0manners for children, this0design is supported by other media such as x-banners, posters, string bags, coloring books, tumblers, stickers, make and0match stickers and crayons.Keyword: Media, Pop-Up Book, Polite Manner